Analysis of the contribution of critical thinking and psychological well-being to academic performance - Guamanga, Miguel H.; Saiz, Carlos; Rivas, Silvia F.; Almeida, Leandro S. (Frontiers in Education, 2024)
This study examines the influence of critical thinking and psychological well-being on the academic performance of first-year college students. It emphasizes the importance of a model of psychological well-being focused on self-acceptance, environmental mastery and purpose in life, along with a critical thinking approach oriented to problem solving and decision making. A total of 128 first-year psychology students from a Spanish public university participated, assessed by means of Ryff's psychological well-being scale (PWBS) and the PENCRISAL critical thinking test, complemented with grades obtained in a critical thinking course. The results show positive correlations between psychological well-being, critical thinking and academic performance, with a stronger relationship between critical thinking and academic performance. However, psychological well-being also plays a significant role in academic performance. The findings highlight the need for holistic pedagogical approaches that combine cognitive skills and personal development to enhance first-year students' learning. Con formato: Portugués (Portugal) Con formato: Español (España) Con formato: Español (España) Con formato: Francés (Francia)